2015
DOI: 10.7869/tg.241
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease prevalence and associated risk factors – A study from rural sector of Maharashtra

Abstract: Prevalence of NAFLD was found be 28.1%. Study confirms that the increased BMI, metabolic syndrome, increased fasting blood glucose and serum triglycerides are potentially strong indicators of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…12 Lavekar A et al (2015) studied 302 individuals with prevalence of NAFLD of 28.1%, which was relatively low compared to our study as we have enrolled only type -2 DM subjects which is one of the proved risk factor for NAFLD. 13 Prabhakar A et al (2017) quoted prevalence of NAFLD was 41.2% in the study group (n=114), which is similar to present study. Prevalence of NAFLD was significantly associated with HbA1c, duration of diabetes and obesity, these findings are comparable with our study.…”
Section: Discussionsupporting
confidence: 91%
“…12 Lavekar A et al (2015) studied 302 individuals with prevalence of NAFLD of 28.1%, which was relatively low compared to our study as we have enrolled only type -2 DM subjects which is one of the proved risk factor for NAFLD. 13 Prabhakar A et al (2017) quoted prevalence of NAFLD was 41.2% in the study group (n=114), which is similar to present study. Prevalence of NAFLD was significantly associated with HbA1c, duration of diabetes and obesity, these findings are comparable with our study.…”
Section: Discussionsupporting
confidence: 91%
“…A study in the Indian state of Haryana, showed prevalence of NAFLD to be 30% in patients from rural villages reporting for US 10. Similarly, another study also conducted in rural India last year showed that the prevalence of NAFLD in patients undergoing routine US was 28.1% 11. Also of note, NAFLD prevalence, even in non-diabetic patients, was found to be high, with an estimate of 24.7% in one study for an urban population 12.…”
Section: Prevalence Of Nafld/nash In South Asiamentioning
confidence: 97%
“…NAFLD comprises a histopathological disease spectrum from bland steatosis to non-alcoholic steatohepatitis (NASH) with significant inflammation and fibrosis, progressing to cirrhosis in approximately 20% of patients with NASH [6]. Increased body mass index (BMI), metabolic syndrome, increased fasting blood glucose, and serum triglycerides are potentially strong indicators of NAFLD [7]. Due to the indolent asymptomatic nature of NAFLD, identifying individuals with advanced disease in whom specific interventions may be required remains a clinical challenge in primary care [1].…”
Section: Introductionmentioning
confidence: 99%